2023
DOI: 10.3393/ac.2022.00234.0033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of C-reactive protein to albumin ratio of the 7th postoperative day on prognosis after laparoscopic colorectal cancer surgery

Abstract: Purpose: C-reactive protein to albumin ratio (CAR) has been utilized as a prognostic factor in various carcinomas. We investigated the relationship between preoperative, postoperative day (POD) 1, and POD 7 CARs and the prognosis of patients with colorectal cancer (CRC).Methods: Three hundred twenty patients with CRC who underwent laparoscopic radical resection between May 2011 and December 2016 were enrolled. Patients were selected into 2 groups, high CAR and low CAR (n=72/group), based on preoperative, POD 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In the study by Kataoka et al [ 6 ], the participants were divided into 2 according to the C-reactive protein to albumin ratio (CAR) in a preoperative examination and at postoperative days 1 and 7 using cut-off values of CAR determined by analyzing the receiver operating characteristic curves for the survival rate. However, the CAR has been reported to be associated with colorectal cancer prognosis [ 12 , 13 ].…”
Section: Comparability Between Comparison Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the study by Kataoka et al [ 6 ], the participants were divided into 2 according to the C-reactive protein to albumin ratio (CAR) in a preoperative examination and at postoperative days 1 and 7 using cut-off values of CAR determined by analyzing the receiver operating characteristic curves for the survival rate. However, the CAR has been reported to be associated with colorectal cancer prognosis [ 12 , 13 ].…”
Section: Comparability Between Comparison Groupsmentioning
confidence: 99%
“…However, the criterion for defining each comparison group was invasion depth, which is not a parameter that we can modify at will. As in the abovementioned study by Kataoka et al [ 6 ], this would involve “comparing apples and oranges.” It would rather be better to compare outcomes according to whether patients underwent laparoscopy in each stratum (LARC or NLARC), and the efficacy of laparoscopy in patients with NLARC should be determined according to differences in the quality of surgical specimens, morbidity, and mortality.…”
Section: Comparability Between Comparison Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kataoka et al [ 8 ] found a distinct association between CAR on postoperative day (POD) 7 and prognosis. They proposed that CAR on POD 7 plays a significant role in the metastatic process of cancer.…”
mentioning
confidence: 99%